Checklist of the native vascular plants of México - José Luis Villaseñor (Revista Mexicana de Biodiversidad)
An updated inventory of the native vascular plants of Mexico records 23,314 species, distributed in 2,854 genera, 297 families, and 73 orders. The flora includes 1,039 species of ferns and lycophytes, 149 gymnosperms, and 22,126 angiosperms. On average, the number of synonyms per species is 1.3 (mode = 1). The number of species places Mexico as the country with the fourth largest floristic richness in the world, although among the non-insular countries, by its number of endemic species (about 50%) is second only surpassed by South Africa. The species distribution among higher taxonomic categories, and the richness and endemism values in the 32 states of Mexico are discussed. This compilation allows us to assess the flora’s contribution to the overall Mexican biodiversity.